Study guides

☆☆

Q: How do you factor 9x squared plus 12x plus 4 - y squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9x2...I guess that means 9x squared ? The problem: 9x(squared)+12x+4 Here's the answer: (3x+2)(3x+2) or even more simplified: (3x+2) squared

9x + 2 = 12x + 14 -3x = 12 x = -4

That doesn't factor neatly. Applying the quadratic equation, we find two real solutions: (-2 plus or minus the square root of 5) divided by 3x = 0.07868932583326327x = -1.4120226591665965

(x+1)(x+8)

9x2 + 8x - 1 = (9x - 1)(x + 1)

Related questions

9x2...I guess that means 9x squared ? The problem: 9x(squared)+12x+4 Here's the answer: (3x+2)(3x+2) or even more simplified: (3x+2) squared

-9x 2 -12x+5 =

Type your answer here... 81

9x + 2 = 12x + 14 -3x = 12 x = -4

That doesn't factor neatly. Applying the quadratic equation, we find two real solutions: (-2 plus or minus the square root of 5) divided by 3x = 0.07868932583326327x = -1.4120226591665965

3(x2 + 3x + 1)

(x+1)(x+8)

9x2 + 8x - 1 = (9x - 1)(x + 1)

(9x)2 +9x/(45x)2 +81= 9+9x/86

You don't need to factor that; you can add them together, since they have the same variable.However, assuming you might mean 81x squared + 9x, you can take out the common factor, which is 9x.

x2 - 9x + 8 = (x-1)(x-8)

People also asked